Structure and luminescent property of a Sm3+ complex containing benzoyltrifluoroacetone and 1,2-bis[(anthracen-9-ylmethyl)amino]ethane ligands - Thi Hien Dinh; Minh Hai Nguyen (Vietnam Journal of Science, Technology and Engineering, 2021)
One of the rare earth coordination compounds that has been studied the most in-depth is -diketonate complexes. This is mostly because they can be rapidly synthesized, are sold commercially, and have a wide range of uses, including photoluminescence and magnetism. The narrow and strong emission of rare earth ions with P-diketonates makes them applicable in optical and electroluminescent devices as well as in luminescence sensors for cations and anions. The synthesis, structure, and luminescent properties of a samarium(III) complex (A2) containing benzoyltrifluoroacetone (HTFPB) and 1,2-bis[(anthracen-9-ylmethyl)amino]ethane (BAAE2) ligands are herein reported. The structure of A2 has been elucidated by infrared spectroscopy and single crystal X-ray diffraction. X-ray crystallographic analysis demonstrated that A2 has a mononuclear structure with a formula of Sm(TFPB)3(BAAE2) in which Sm3+ ion is coordinated to six O-atoms from three TFPB ligands and two N-atoms from one ancillary ligand (BAAE2). The substantial absorptions generated by the -diketonate and anthracenyl fragments are confirmed by UV-Vis measurements. The data show that A2 strongly absorbs in the region of 220-400 nm. Nonetheless, A2 gives poor emission due to a quenching effect of the anthracenyl moiety.